The Automated Processing of Arabic Morphology Reality and Perspectives - Laib, Ahcene (Journal of Human Sciences, 2022)
This research paper aims to shed light on a recent topic concerning the automated processing of Arabic morphology, It was chosen in this study because it represents one of the language levels, it mediates between the phonetics and grammatical levels , and it contributes in the formation of The Arabic Word Structure. In the introduction, the study dealt with the artificial intelligence, and its importance in studying the language. In the presentation, the study presented the automatic analysis of the Arabic morphology, then, it dealt with the most important problems that the morphological analyzer is facing, as well, explaining its most prominent uses, mentioning the most important morphological analyzers of the Arabic language, and showing how to benefit from the automated morphological analyzer in studying the holy Quran’s words. .The research ended with a conclusion that included the most important results.